2009
DOI: 10.1021/jf802559z
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Induced Whey Protein Gels: Protein−Protein Interactions and Functional Properties

Abstract: Heat-induced gelation (80 degrees C for 30 min or 85 degrees C for 60 min) of whey protein concentrate (WPC) solutions was studied using small deformation dynamic rheology, small and large deformation compression, and polyacrylamide gel electrophoresis (PAGE). The WPC solutions (15% w/w, pH 6.9) were prepared by dispersing WPC powder in water (control), 1% (w/w) sodium dodecyl sulfate (SDS) solution, and N-ethylmaleimide (NEM) solution at a protein/NEM molar ratio of 1:1 or in 10 mM dithiothreitol (DTT) soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 15 publications
0
42
0
Order By: Relevance
“…In comparison, sWPC-80 exhibited a similar SDS-PAGE profile with individual subunits of α-lactalbumin, β-lactoglobulin, and BSA, which indicated that superfine grinding did not influence the protein distribution of WPC. Furthermore, addition of β-mercaptoethanol broke existing intramolecular disulfide linkages and prevented formation of new intermolecular disulfide bonds, restricting protein aggregation to only non-covalent linkages (24). SDS-PAGE results explained that superfine grinding could not induce non-covalent associations of WPC molecules, but could not indicate the formation of intermolecular disulfide bonds.…”
Section: Resultsmentioning
confidence: 98%
“…In comparison, sWPC-80 exhibited a similar SDS-PAGE profile with individual subunits of α-lactalbumin, β-lactoglobulin, and BSA, which indicated that superfine grinding did not influence the protein distribution of WPC. Furthermore, addition of β-mercaptoethanol broke existing intramolecular disulfide linkages and prevented formation of new intermolecular disulfide bonds, restricting protein aggregation to only non-covalent linkages (24). SDS-PAGE results explained that superfine grinding could not induce non-covalent associations of WPC molecules, but could not indicate the formation of intermolecular disulfide bonds.…”
Section: Resultsmentioning
confidence: 98%
“…Denaturation of B-LG leads to disulfide interchange reactions and a redistribution of the -SH groups (Monahan, German, & Kinsella, 1995), hence it influences the ability to form heat induced gel networks. Also, non-covalent linkages are involved in the formation of the gel network, and it has been reported that an increased amount of noncovalent association leads to increased stiffness (modulus) of the formed gel, whereas an increased amount of disulfide linkages increases the fracture strain of the gel (Havea, Watkinson, & Kuhn-Sherlock, 2009). …”
Section: Whey Proteins and Gel Network Formationmentioning
confidence: 99%
“…Whey is used for e.g. texture enhancement in formulated products such as processed meat, bakery products and dairy products, and the utilization has progressed significantly due to extensive research and interest in understanding whey proteins as functional ingredients (Havea, Watkinson, & Kuhn-Sherlock, 2009;Kresic, Lelas, Jambrak, Herceg, & Brncic, 2008). …”
Section: Introductionmentioning
confidence: 99%